Main aspects of surgical treatment in patients with infective endocarditis. - Milvio B. Ramírez López (Revista Cubana de Cardiología y Cirugía Cardiovascular, 2015)
In 1965 he was operated the first patient suffering from an infectious endocarditis (IE), then the date, advances in diagnosis, antibiotic, techniques cardiopulmonary bypass (CPB), myocardial protection and postoperative care have enabled more effective reconstructions cardiac lesions caused by this disease and increased survival.Mentioned most frequent indications for surgery in the EI; review the surgical techniques in native mitral valve and mitral prosthesis, insisting on the valve repair, mitral homograft usefulness of biological prostheses and stents.In native IE valve or prosthetic aortic valve replacement value, cryopreserved homograft, tissue valves, conduits and reconstruction with pericardium. Valve Repair of choice for tricuspid EI and EI for the complete extraction electrodes CEC. Summary of our results in 163 patients operated.